2018
DOI: 10.15376/biores.14.1.592-606
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various pretreatment methods on sugar and ethanol production from cellulosic water hyacinth

Abstract: Effects of acid, alkali, ionic liquid (IL), and microwave-alkali pretreatments on cellulosic water hyacinth (WH) were investigated based on the total reducing sugars (TRS) and ethanol production. For the first time, IL pretreatment with (1-Ethyl-3-methylimidazolium acetate ([EMIM][Ac]) was used for WH, and the efficiency was compared with the other methods. Cellulase and Saccharomyces cerevisiae were fermented together for 72 h. Based on the results, all pretreatment methods effectively increased the sugar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The untreated WH consisted of 16.4% ± 0.35% cellulose, 32.7% ± 0.14% hemicellulose, and 5.7% ± 0.05% lignin, as reported in previous research (Rezania et al 2019). Narra et al (2017) reported 38.01% ± 1.26% cellulose, 24% ± 0.74% hemicellulose, and 9.50% ± 0.84% lignin in WH dry matter.…”
Section: Compositional Analyses Of the Wh After Different Pretreatmentssupporting
confidence: 73%
See 1 more Smart Citation
“…The untreated WH consisted of 16.4% ± 0.35% cellulose, 32.7% ± 0.14% hemicellulose, and 5.7% ± 0.05% lignin, as reported in previous research (Rezania et al 2019). Narra et al (2017) reported 38.01% ± 1.26% cellulose, 24% ± 0.74% hemicellulose, and 9.50% ± 0.84% lignin in WH dry matter.…”
Section: Compositional Analyses Of the Wh After Different Pretreatmentssupporting
confidence: 73%
“…In this study, four types of pretreatments were performed: acid, alkali, IL, and microwave-alkali. The pretreatment specifications were like those in a previous study (Rezania et al 2019). The alkali pretreatment was performed at four different concentrations of NaOH (4%, 5%, 6%, and 7%) at 110 °C and a pH of 5.…”
Section: Different Pretreatment Methodsmentioning
confidence: 99%